Teachers' Readiness and Attitudes Toward the Implementation of Climate Change Education in Southeast Asia - Jaelani, Ahmad; Djayaningrat, Dion Winarno (Journal of Science and Mathematics Education, 2025)
The escalating impacts of climate change have underscored the urgent need for integrating Climate Change Education (CCE) into school curricula, particularly in vulnerable regions such as Southeast Asia. This study explores the readiness and attitudes of teachers across selected Southeast Asian countries toward the implementation of CCE in formal education. Utilizing a mixed-methods approach, the research surveyed 350 teachers from Indonesia, Malaysia, Thailand, and the Philippines, and conducted in-depth interviews with 20 educators. The findings reveal a moderate level of readiness among teachers, primarily influenced by institutional support, availability of resources, and prior training. Attitudinally, the majority of respondents expressed a positive outlook on the integration of CCE, recognizing its importance in fostering environmental awareness and sustainable behavior among students. However, significant barriers were identified, including lack of professional development programs, insufficient instructional materials, and curriculum constraints. The study highlights the necessity of multi-stakeholder collaboration involving governments, educational institutions, and NGOs to develop structured training programs and supportive policies. By identifying the current gaps and opportunities, the research provides actionable insights for policy-makers and educational planners aiming to strengthen the role of teachers in combating climate change through education. Enhancing teacher capacity is crucial for cultivating a climate-literate generation prepared to face environmental challenges in the region.